From Apotheosis to Reverse Conversion: A Posthuman Reading of Euripides’ and Pasolini’s Medea - Barcaro, Andrea (Imaginations)

(untitled) (York University, 2024)
Medea is an ancient mythical figure who has caught the imagination of artists and authors across the centuries. In this essay, I focus on Euripides’ 5th-century BC eponymous tragedy and Pasolini’s 1969 cinematic adaptation. Through a posthuman reading of Medea, I propose that in Euripides the heroine sheds her humanity and embraces divinity in her final apotheosis. In Pasolini’s film, on the other hand, we witness a reverse conversion, a journey towards a loss of the sacred and a spiritual catastrophe. In my analysis, I explore how posthuman forms of subjectivity embrace monstrosity to emphasise the divine power of alterity. I propose that, by deactivating normative discourses and making possible resistance to norms, posthuman subjectivities can be a powerful tool to break the spell of the present and create productive alternatives to the seemingly timeless dominance of global capitalism.